Analysis of Insulation Materials for Cryogenic Hydrogen Storage Tank for Light Aircraft - Nazri, Muhammad Aiman Hakimi; Mohd Yunos, Siti Nur Mariani (Progress in Aerospace and Aviation Technology, 2025)
This study investigates the influence of insulation material on the performance of a cryogenic hydrogen storage tank designed for a light aircraft. A cylindrical pressure tank with hemispherical end domes was sized for integration into the aft cabin of a Cessna 172 aircraft. The tank and insulation layers were modelled in SolidWorks 2022. Static structural and steady-state thermal analyses were performed for fiberglass and aerogel as the insulation materials. The mass characteristics, stress distribution and thermal behaviour of the two configurations were compared. For the same storage pressure and volume, the total mass of the fiberglass-insulated tank was about 38.9 kg, whereas the aerogel-insulated tank had a reduced total mass of approximately 15.9 kg, representing a reduction of more than 50% in the system mass. In both cases, the von Mises stress field was dominated by the cylindrical shell, with lower stresses in the domes, and no adverse stress concentrations were introduced by replacing the fiberglass with aerogel. Thermal analysis showed that the fiberglass configuration developed a higher heat flux and significant temperature gradients, leading to an estimated hydrogen boil-off rate of 2019.2 g/h. By contrast, the aerogel configuration maintained most of the internal surface close to the cryogenic temperature, with a much lower heat flux of 0.2223 W/m², a total heat transfer rate of 0.2223 W, and a boil-off rate of only 3.6 g/h. These findings indicate that aerogel offers substantial advantages over fiberglass for cryogenic hydrogen storage in light aircraft. Therefore, it merits further investigation in more detailed tank- and aircraft-level design studies.